Antibacterial-enhanced Synthetic Stainless Steel, Hydroxyapatite, and Polylactic Acid in Bioactive Screw Systems for Safe Bone Healing - Prima, Eka Cahya; Melati, Putri Sekar; Arifah, Fina Nurul; Septiyanto, Arifin; Nurahman, Arip; Budiatin, Aniek Setiya; Herdianto, Nendar (Islamic Research, 2025)
Bone fractures are rising worldwide due to aging populations and increased trauma, creating demand for implants that overcome infection, delayed healing, and poor osteointegration. Multifunctional biomaterials, especially PLA–HA Bioxcrew systems, offer integrated mechanical support with antibacterial, anti-inflammatory, and osteogenic functions while remaining biocompatible. Implant-associated infections driven by Staphylococcus aureus and Gram-negative bacteria persist because of biofilm formation and chronic inflammation. Bioxcrew advancements address these barriers through metal-ion doping, nanoscale surface engineering, and incorporation of antimicrobial agents into biodegradable polymer matrices, enabling controlled ion release, immune modulation, stem-cell recruitment, and improved bone regeneration. Stainless steel provides strength, hydroxyapatite enhances biological integration, and PLA enables safe degradation and localized drug delivery, making their hybridization ideal for next-generation implants. Using a narrative–integrative review of peer-reviewed literature from 2018 to 2025, this study synthesizes trends in antibacterial strategies and regenerative performance. Findings show that hybrid Bioxcrew platforms significantly reduce infection risk and enhance functional bone healing.